Developing Grit, Motivation, and Resilience: To Give Up on Giving In - Whitfield, Karen M. (Pharmacy (Basel), 2021)
Developing grit, motivation, and resilience within the pharmacy workforce has become a topic of increasing interest, heightened by the recent COVID-19 pandemic. Even prior to the global pandemic, the health care field has been associated with a rapidly changing, challenging, and pressured work environment that can often lead to stress and burnout. Developing resilience in health care workers has been identified as a strategy to combat burnout by improving their ability to thrive in stressful situations, thus enhancing physical and mental well-being. In this commentary, we consider the use of a resilience framework that encompasses the overlapping attributes of emotional balance and physical and mental strength to develop resilience. The importance of finding purpose and meaning is also explored within the framework, as well as the association between grit, motivation, autonomy, mastery, and connection. Practical strategies and reflections are outlined to challenge, inspire, and motivate the development of grit and resilience, in order to combat the challenges faced by pharmacists in a constantly changing health care system.